Analysis in 3D Rendering Modeling Processing using Autodesk Maya and Blender Software - Suhaili Muhammad; Khairusani Nabila Fitri (MBI, 2023)
Many alternative software for producing 3D animation. Some of them are Autodesk Maya and Blender. In the animation pipeline there are three main stages, namely pre-production, production and post-production. In post-production there are rendering or rendering steps. Rendering is the processing of all animated scene objects in the form of modeling data, movement, texturing, lighting, sound and so on into a certain output which is the final appearance of an animated video. In this research, we analyze the performance of the two 3D software above in rendering an object. Rendering using Autodesk Maya takes 45 seconds. While the results of rendering using Blender can complete in 1 second. In terms of rendering quality, Autodesk Maya produces more detailed texturing quality.